Provision of Thai herbal recommendation based on an ontology - Kato, Takumi; Maneerat, Noppadol; Varakulsiripunth, Ruttikorn; Izumi, Satoru; Takahashi, Hideyuki; Suganuma, Takuo; Takahashi, Kaoru; Kato, Yasushi; Shiratori, Norio (My University, 2010)
In Thailand, most of people like to use Thai herbs for their traditional medical treatments. However, since there are various sorts of Thai herbs, and the Thai herbal knowledge is complicated, it is difficult to find an appropriate one for each health condition. In order to help people to find suitable Thai herbs to cure the diseases, we have developed a system to provide herbal recommendations to users regarding their symptoms. In the development, we represented the Thai herbal knowledge in an ontology, and extracted new facts based on the ontology. Finally, the system provides appropriate herbal recommendations to users based on extracted facts and the ontology. This paper shows how we represented Thai herbal knowledge in an ontology, and how we extract the new facts based on the ontology, as well as how the system provides herbal recommendations to users. © 2010 IEEE.
Keywords: Inference; Knowledge representation; Ontology; Thai herb